2023
DOI: 10.15252/embr.202256660
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐induced transmembrane protein 3 (IFITM3) limits lethality of SARS‐CoV‐2 in mice

Abstract: Interferon-induced transmembrane protein 3 (IFITM3) is an antiviral protein that alters cell membranes to block fusion of viruses. Conflicting reports identified opposing effects of IFITM3 on SARS-CoV-2 infection of cells, and its impact on viral pathogenesis in vivo remains unclear. Here, we show that IFITM3 knockout (KO) mice infected with SARS-CoV-2 experience extreme weight loss and lethality compared to mild infection in wild-type (WT) mice. KO mice have higher lung viral titers and increases in inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Human IFITM3 deficiencies are associated with heightened severity of influenza, and data are emerging that IFITM3 deficiencies are a risk factor for severe COVID-19 [16][17][18][19][20] . Indeed, we and other groups have observed that Ifitm3 -/mice experience more severe influenza virus and SARS-CoV-2 infections, mimicking human IFITM3 defects 15,16,[21][22][23] .…”
Section: Mainmentioning
confidence: 63%
See 2 more Smart Citations
“…Human IFITM3 deficiencies are associated with heightened severity of influenza, and data are emerging that IFITM3 deficiencies are a risk factor for severe COVID-19 [16][17][18][19][20] . Indeed, we and other groups have observed that Ifitm3 -/mice experience more severe influenza virus and SARS-CoV-2 infections, mimicking human IFITM3 defects 15,16,[21][22][23] .…”
Section: Mainmentioning
confidence: 63%
“…Beneficial mutations that allow the virus to replicate more efficiently are enriched by outcompeting the parental virus and other mutants. Indeed, influenza virus and several other viruses replicate to higher titers in Ifitm3 -/versus WT mice 15,16,[21][22][23][32][33][34] , which represents a plausible mechanism for enhanced adaptation in these animals 31 . In our current study, mutations in the 2009 pandemic H1N1 virus passages that drive adaptation in mice were primarily observed in the viral polymerase subunits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IFITM proteins provide constitutive and interferon-induced antiviral protection in many cell types by inhibiting the virus-cell membrane fusion step required for entry 47,48 . While it is established that murine IFITM3 restricts SARS-CoV-2 infection and limits viral disease in vivo 49,50 , the roles played by human IFITM proteins during SARS-CoV-2 infection have remained controversial. For example, it was demonstrated that IFITM proteins can inhibit SARS-CoV-2 infection in endosomes but can promote infection at the cell surface 51,52 .…”
Section: Resultsmentioning
confidence: 99%
“…Lungs were embedded in paraffin, sectioned, stained, and imaged by Histowiz (Histowiz.com, Brooklyn, NY, USA). Unbiased electronic quantification of resultant images was performed using ImageJ software and the color deconvolution method as described previously 9,[35][36][37] .…”
Section: Methodsmentioning
confidence: 99%